Prediction Model of Food Security on Heart Disease Incidence in Indonesia - Saifudin Zukhri, Sumardiyono, Ratih Puspita Febrinasari,Budiyanti Wiboworini (South Eastern European Journal of Public Health, 2025)
Food security is one of main health problems in Indonesia. Previous studies have shown a correlation between food insecurity and heart disease, but it cannot be predicted whether food insecurity is a risk factor for heart disease. Purpose. This study aims to determine the relationship between food insecurity and incidence of heart disease among Indonesian aged 15–65 years in a cohort over 14 years. Method. The subjects were 13,464 Indonesian residents aged 15–64 years. Subjects were followed for 14 years to find out the incidence of heart disease.To reveal relationship between two variables above, General Structural Equations Model (GSEM) was used. Results : from GSEM analysis indicate that food security status is indirectly related to the incidence of heart disease. Food insecurity increases risk of overweight and hypercholesterolemia by 0.18 and 0.55 units respectively compared to food insecurity status. Excess body weight and hypercholesterolemia become mediators between food security and hypertension, stroke, and diabetes mellitus. Direct causal factors (p<0.004) of heart disease in Indonesian population are old age (43–65 years), stroke, hypertension, and diabetes mellitus. Conclusion. Food safety status is indirectly related to heart disease. Obesity, diabetes mellitus, and hypertension are mediators between food security status and heart disease.